2007
DOI: 10.1097/inf.0b013e3180618bd6
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Prevention of Mother-to-Child Transmission of Human Immunodeficiency Virus Type 1 in Latin America and the Caribbean: The Nisdi Perinatal Study

Abstract: Cases of mother-to-child transmission (MTCT) of human immunodeficiency virus type 1 (HIV-1) in a prospective cohort study in Latin America and the Caribbean were analyzed. Eight of 820 eligible infants became infected [transmission rate, 0.98% (95% CI = 0.45-1.96%)]. Five cases (62%) represented missed opportunities for prevention of MTCT of HIV-1, suggesting the need for ongoing training and education of clinicians regarding prevention of MTCT of HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The results of the present study are consistent with previous studies of MTCT of HIV-1 conducted over the past 8 years in Europe [8,9], the USA [10,11], Africa [12], and Latin America and the Caribbean [2,13]. These studies identified various missed opportunities for prevention of infection, which included late or no HIV-1 testing [10–12]; late or no initiation of prenatal care or maternal antiretrovirals [2,8,10,11]; limited or no use of maternal antiretroviral regimens [2,9,11,13]; poor control of maternal VL during pregnancy [2]; and lack of ECD [2,11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study are consistent with previous studies of MTCT of HIV-1 conducted over the past 8 years in Europe [8,9], the USA [10,11], Africa [12], and Latin America and the Caribbean [2,13]. These studies identified various missed opportunities for prevention of infection, which included late or no HIV-1 testing [10–12]; late or no initiation of prenatal care or maternal antiretrovirals [2,8,10,11]; limited or no use of maternal antiretroviral regimens [2,9,11,13]; poor control of maternal VL during pregnancy [2]; and lack of ECD [2,11].…”
Section: Discussionsupporting
confidence: 92%
“…These studies identified various missed opportunities for prevention of infection, which included late or no HIV-1 testing [10–12]; late or no initiation of prenatal care or maternal antiretrovirals [2,8,10,11]; limited or no use of maternal antiretroviral regimens [2,9,11,13]; poor control of maternal VL during pregnancy [2]; and lack of ECD [2,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of the AIDS cases among children (<13 years old) are attributable to mother-to-child-transmission (MTCT). Although the rate of vertical transmission has been declining, the implementation of antenatal HIV screening and timely management of infected pregnant women varies across the country due to disparities of health care access, suggesting missed opportunities for prevention [22-24]. …”
Section: Introductionmentioning
confidence: 99%
“…Published reports regarding missed opportunities for prevention of mother-to-child transmission of HIV from Latin America and the Caribbean (21, 22) Europe (23) and the U.S. (24) found late initiation of prenatal antiretroviral therapy, poor control of viral load, late HIV diagnosis and lack of elective cesarean delivery as common factors resulting in mother-to-child transmission. These findings are similar in our case series.…”
Section: Discussionmentioning
confidence: 99%